2022
DOI: 10.48048/tis.2022.2159
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Combination Compound (Cyclopamine) Isolated from Veratrum californicum and 5-FU Acting as Anti-invasive and Initiator of Intrinsic Apoptosis Mechanism against Aggressive Type Colorectal Cancer Cells

Abstract: Characteristics of programmed cell death are generally regarded as defined by cell outgrowth or cellular aging and distinct morphological characteristics featuring nuclear condensation and formation of apoptotic bodies. Apoptosis is considered to have a function at cellular level and is essential to long-lived cell differentiation undergoing senescence and apoptosis. Inappropriate apoptosis is a factor that results in serious conditions, causing multiple disease progression as well as cancer. The ability to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In contrast, BCL2 and Cyclin D1 gene expression were not decreased in our study by cyclopamine treatment. Although Cyclin D1 is typically thought of as an oncoprotein, more research should be done on the impact of alterations in its expression in various malignancies [17]. Despite the fact that Cyclin D1 expression has been found to rise in many cancers, some researches have suggested that excessive Cyclin D1 expression may inhibit cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, BCL2 and Cyclin D1 gene expression were not decreased in our study by cyclopamine treatment. Although Cyclin D1 is typically thought of as an oncoprotein, more research should be done on the impact of alterations in its expression in various malignancies [17]. Despite the fact that Cyclin D1 expression has been found to rise in many cancers, some researches have suggested that excessive Cyclin D1 expression may inhibit cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with cyclopamine was associated with an increase in some of apoptotic genes, inhibition of colon formation, a little decline in metabolic activity of cells, and slight increase in apoptotic cells. According to the results of previous studies, Cyclopamine treatment on the colorectal cancer cell lines alters the morphology of cells, reduces viability, impairs cell migration ability, and eliminates chemotherapy resistance [17]. Additionally, it was discovered that cyclopamine decreases the expression of SMO and GLI1, which inhibits the Shh pathway and may potentially decrease the expression of self-renewal genes in colorectal cancer [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation